Reduced Plasma Lipid Mediators Are Directly Associated with Low Vitamin A Status in Women from Western Samar, Philippines. (29th May 2020) - Rosario, Rodrigo; Engle-Stone, Reina; Haskell, Marjorie; Brito, Alex; Agrawal, Karan; Fanter, Rob; Newman, John; Frano, Michael La
Abstract: Objectives: Vitamin A (VA) is an essential micronutrient that plays a key role in many biological processes, including growth, vision, immunity and reproduction. While evidence has been established to support these mechanisms, new studies suggest there may be more signaling compounds that are impacted by VA status. Lipid mediators, such as oxylipins and lysophospholipids, are signaling compounds that, in response to biological stimuli, exhibit regulatory effects on inflammation, immune function, vascular tone, and other systems. The objective was to investigate differences in lipid mediators associated with VA status. Methods: In this cross-sectional study, blood samples from women in Western Samar, Philippines, were selected based on plasma retinol concentration indicating adequate ( n  = 5) or low ( n  = 5) VA status (retinol < 0.7 μmol/L). Retinol was measured using an Agilent 1200 HPLC-DAD. Oxylipin, endocannabinoid, bile acid, and lipidomics assays were analyzed on a Waters Acquity UPLC and detected using multiple reaction monitoring on a Sciex 4000 QTRAP. Data were adjusted for covariates related to the acute phase response, age, and BMI. Results: Twenty-four lipid mediators were lower in the low VA status group ( P  < 0.05). These lipid mediators included the arachidonic acid-derived oxylipins' lipoxin A4 and 6-trans-LTB4 formed via lipoxygenases (LOX), as well as the cyclooxygenase (COX) product PGD2. Several LOX and soluble epoxide hydrolase (sEH) oxylipins produced from eicosapentaenoic acid and the acylethanolamides LEA and PEA were lower ( P  < 0.05) in individuals with low plasma retinol levels. Numerous phospholipids and sphingolipids were also lower ( P  < 0.05) with decreased VA status, including two lysophosphatidylcholines, three lysophosphatidylethanolamines, two phosphatidylcholines, and two sphingomyelins. Conclusions: In this exploratory study, VA status was directly associated with lipid mediator concentrations. Future studies testing the biological impact of lipid mediator changes with varying levels of VA status are necessary. Funding Sources: NIH U24 DK097154, USDA Intramural Project 2032–51, 530-022–00D, NIH T32-GM008799, Cal Poly CAFES SURP.